Three dimensional numerical analysis of inducer about suppression of cavitation instabilities by asymmetric slits on blades. Issue 3 (March 2019) - Kamikura, Y; Kobayashi, H; Kawasaki, S; Iga, Y
Abstract: Cavitation is the phenomenon in which liquid evaporates and vapor bubbles occur in the low pressure region such as a pressure of liquid is roughly less than saturated vapor pressure. The cavitation causes a bad in uence such as vibration, noise, and a decline in performance on the turbomachineries. Moreover, the unsteady cavitation brings the oscillations in the turbomachinery which is called cavitation instabilities. In our laboratory, the suppression technique of the cavitation instabilities by using asymmetric slits on each blade has been investigated as a simple method. From the numerical results, it was con rmed that the cavitation instabilities are completely suppressed by a certain arrangement of asymmetric slits. In this study, the three-dimensional numerical analysis of the inducer was conducted. Two inducers which have asymmetric slits were used for this calculation. Moreover, to consider the asymmetric slit for effectiveness of cavitation instabilities, transient analysis are conducted. Although arranging the asymmetric slit cannot completely suppress the phenomenon, the cavity volume becomes smaller than without slit in all blades. This indicates that arranging asymmetric slits has the possibility to weaken the amplitude of cavitation instabilities.